PEMBELAJARAN MATEMATIKA BERBASIS ETHNOMATEMATIKA DI SATUAN PENDIDIKAN - Melkior Wewe; Maria Oktavia Dede Rua; Maria Adriana Fono (Jurnal Ilmiah Mandalika Education (MADU), 2024)
Ethnomathematics is something that can be used to combine mathematics with culture. So that culture & mathematics can go hand in hand & be more easily understood by students. The aim of this research is to find out what role ethnomathematics plays in mathematics learning and to be able to change students' negative defects regarding mathematics. The research method used is the study method (library research) itself, which is a method of collecting, studying, & knowing theories based on various kinds of literature contained in a study. This research is secondary data which is originally based on published research articles and is related using a predetermined title. Data collected using free, involved listening, speaking and note-taking techniques. The results of this research can determine the crucial role of ethnomathematics in mathematics learning. The conclusion of this research is that we can understand the role of ethnomathematics in mathematics learning, namely that ethnomathematics can connect mathematics with culture, change negative defects about mathematics, make students more enthusiastic about participating in mathematics learning and can train teachers to be creative & innovative in expressing mathematical material. using existing culture.